2016
DOI: 10.3390/s16121995
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Solar Tracking System Using the Brightest Region in the Sky Image Sensor

Abstract: Solar energy is certainly an energy source worth exploring and utilizing because of the environmental protection it offers. However, the conversion efficiency of solar energy is still low. If the photovoltaic panel perpendicularly tracks the sun, the solar energy conversion efficiency will be improved. In this article, we propose an innovative method to track the sun using an image sensor. In our method, it is logical to assume the points of the brightest region in the sky image representing the location of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…The last case of Figure 7 e illustrates that the circumference of the Sun is affected by the intense overcast, but despite this, in the next shot ( Figure 7 f) we can see that the image from the image sensor is again clear, as if it were not cloudy. With these tests we can verify that the filter performs a perfect job at attenuating perturbations presented in this type of application [ 29 ]. The type of lens plays an important role in the capture of the image in the vision sensors, as demonstrated in the work of Lee et al [ 24 ] which showed that the aperture of the lens helps improve the accuracy of the detection of the Sun.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last case of Figure 7 e illustrates that the circumference of the Sun is affected by the intense overcast, but despite this, in the next shot ( Figure 7 f) we can see that the image from the image sensor is again clear, as if it were not cloudy. With these tests we can verify that the filter performs a perfect job at attenuating perturbations presented in this type of application [ 29 ]. The type of lens plays an important role in the capture of the image in the vision sensors, as demonstrated in the work of Lee et al [ 24 ] which showed that the aperture of the lens helps improve the accuracy of the detection of the Sun.…”
Section: Resultsmentioning
confidence: 99%
“…For closed-loop systems, differential light sensors based on phototransistors [ 14 , 15 , 16 ], photo resistors [ 9 , 17 , 18 ] photovoltaic cells [ 19 , 20 ] and image processing based systems [ 21 , 22 , 23 , 24 , 25 ] are used. For the third strategy, a hybrid is used, on which the Sun´s position is calculated to locate it to a nearby focus point, and from then on, the sensor itself makes a precise adjustment [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seperti halnya sumber cahaya matahari, lampu akan menghasilkan sinar yang menyebar. Segmentasi lampu ketika menyala yang salah akan menghasilkan area lamp lebih besar dari pada sebenarnya yaitu ketika padam, disebabkan oleh sebaran cahayanya ikut diartikan sebagai nyala lampu [7].Penelitian ini bertujuan untuk membandingkan segmentasi lampu ketika padam dan ketika menyala sehingga dapat dijustifikasi akurasi dari sistem yang dibuat.…”
Section: Pendahuluanunclassified
“…Bobot telur ayam diperoleh dari perhitungan luasan hasil segmentasi telur ayam yang dihasilkan. Disisi lain, pencitraan nyala lampu dapat dianalogikan dengan pencitraan sinar matahari [7,10,11]. Keduanya menggunakan thresholding untuk mendapatkan citra sinar matahari.…”
Section: Pendahuluanunclassified
“…In presented paper there is a Dual axis solar tracker which has two degrees of freedom acting as axes of rotation for the panel. Axes are kept normal to each other by rotating simultaneously longitude and latitude, they are also capable of pointing the sun's radiation perpetually [6][7]. By referring another research in which sensing of sun's position is been done through two stages, first stage which is also termed as direct sensing is been performed via aid of set of LDR sensors as output tuning for trimming both the angles which are azimuth and altitude.…”
Section: Introductionmentioning
confidence: 99%